EFFICACY OF DRUG ALVET-SUSPENSION WHEN STRONGYLATOSIS THE DIGESTIVE TRACT OF SHEEP UNDER CONDITIONS WEST KAZAKHSTAN REGION - W. J. Kuzibaeva; R. S. Kamaliev (Российский паразитологический журнал, 2016)
Objective of research. The aim of the study was to examine the effectiveness of alvet-suspension when strongylatosis the digestive tract of sheep. Materials and methods. Test alvet-suspension was carried out in LLP "Diet" West Kazakhstan region 40 sheep, spontaneously infested strangulate of the digestive tract. Sheep were divided into 4 groups of 10 animals each. The sheep of the first group asked alot oral-suspension in a dose of 5 mg/kg on ET rate of 0.05 ml/kg Animals of the second group was administered ivermec 1% solution intramuscularly in a dose of 0.2 mg/kg at ET rate of 0.02 ml/kg of Levamisole was administered subcutaneously to sheep 3-the third group at a dose of 7.5 mg/kg at a rate of 0.1 ml/kg Animals of the fourth group was used and served as control. The effectiveness of the drugs considered through 18 days after deworming according to the results Koprivshtitsa studies by flotation using counting chambers WIKIS and efficiency calculation type "control test". Results and discussion. Extendedrequest (EE) and intensifications (IE) alvita-suspension was respectively 90 and 96 %. 9 out of 10 treated Alvestam-suspension of the first group of animals freed from worms. In the second group, which used ivermec, worming released 9 of the 10 treated animals. EE and IE was 90 and 95 %. In the third group, which used the levamisole, the worms have released 7 of the 10 treated animals. EE and EI were 70 and 78 %. The low efficiency of levamisole compared with other drugs can be explained by the development of resistance to the action of strongest of the digestive tract, as this anthelmintic was used previously. During the experience the invasion of animals of the control groups were not significantly changed. Alvetsuspension 10 % in a dose of 5 mg/kg in a production environment is a highly effective drug when strongylatosis the digestive tract of sheep.